CFD Simulation of the Discharge Flow from Standard Rushton Impeller - Bohuš Kysela; Jiří Konfršt; Ivan Fořt; Zdeněk Chára (International Journal of Chemical Engineering)
The radial discharge jet from the standard Rushton turbine was investigated by the CFD calculations and compared with results from the Laser Doppler Anemometry (LDA) measurements. The Large Eddy Simulation (LES) approach was employed with Sliding Mesh (SM) model of the impeller motion. The obtained velocity profiles of the mean ensemble-averaged velocity and r.m.s. values of the fluctuating velocity were compared in several distances from the impeller blades. The calculated values of mean ensemble-averaged velocities are rather in good agreement with the measured ones as well as the derived power number from calculations. However, the values of fluctuating velocities are obviously lower from LES calculations than from LDA measurements.